2019
DOI: 10.1111/dom.13670
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid and the cardio‐renal effects of SGLT2 inhibitors

Abstract: Sodium/glucose co-transporter-2 (SGLT2) inhibitors, which lower blood glucose by increasing renal glucose elimination, have been shown to reduce the risk of adverse cardiovascular (CV) and renal events in type 2 diabetes. This has been ascribed, in part, to haemodynamic changes, body weight reduction and several possible effects on myocardial, endothelial and tubulo-glomerular functions, as well as to reduced glucotoxicity. This review evaluates evidence that an effect of SGLT2 inhibitors to lower uric acid ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 129 publications
(230 reference statements)
4
123
0
5
Order By: Relevance
“…A recent clinical trial suggested that urate-lowering therapy might be associated with maintaining or improving eGFR in patients with chronic kidney disease without proteinuria [24]. Since SGLT2 inhibitors reduce serum uric acid levels, it is postulated that the urate-lowering effect of SGLT2 inhibitors may assist in retarding the progression of chronic kidney disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical trial suggested that urate-lowering therapy might be associated with maintaining or improving eGFR in patients with chronic kidney disease without proteinuria [24]. Since SGLT2 inhibitors reduce serum uric acid levels, it is postulated that the urate-lowering effect of SGLT2 inhibitors may assist in retarding the progression of chronic kidney disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational and interventional studies have shown that uric acid acts as a modifiable risk factor in the progression of chronic kidney disease for type 2 diabetes 1,2 . This is also true for those diabetes patients with lesser degrees of hyperuricemia.…”
Section: Benefitsmentioning
confidence: 91%
“…Hyperuricemia and the risk of gout are commonly seen in patients with type 2 diabetes. It has also been reported that chronically elevated circulating uric acid concentrations are associated with an increased risk of hypertension, cardiovascular disease and chronic kidney disease, all of which are known diabetes‐associated complications 1,2 .…”
Section: Benefitsmentioning
confidence: 99%
See 2 more Smart Citations